Sistem pengajaran kendiri sejarah berasaskan modul teras cabang Shaharom - Supangat, Ehwan (2005)
Technology advancement has given a great impact on education. Whereby e-learning becomes the main base to conventional approach in teaching and learning. Thus “ Sistem Pengajaran Kendiri Sejarah “Self-Access Learning via the website to help students to excel in Paper 1 Sejarah SPM. The Subject is a compulsory in SPM paper. It covers the form four and form five syllabus. It has 40 questions and student are not really keen to learn this subject because its current approach and a vague/general topic which make it difficult. There for MPK Sejarah has combined MPK approach base on Module Teras Cabang introduced by Dr. Shaharom Nordin in 1994. This approach is more effective compared to Portal Pendidikan. The SPM Candidates are the main target. They can access the reference notes, model test paper and any related information at any time. MPK Sejarah approach has been introduced in stages to ensure its effectiveness can be improved from time to time.